The publishing world of Aurora Venturini (Revista de Crítica Literaria Latinoamericana, 2016)
This article aims at examining the distinct editorial periods in Argentine writer Aurora Venturini’s (1921-2015) literary work. In order to achieve this objective, we analyze different kinds of sources: the editions of her books, articles in the press, oral testimonies, letters and other documents from Venturini’s personal archive. During the first editorial period, which goes from 1942 to 2007, most of her literary work was published in author’s editions and without a significant reward in the world of letters. In 2007, she won the Página/12 New Novel award, which signified a radical turn in her career. The second period, defined from this point to 2015, is when Venturini’s literary work started to be visible due to her link with Página/12 newspaper and the renowned publishing company Penguin-Random House.
Keywords: Aurora Venturini; editorial periods; literary award; publishing market